Culturas escolares e adolescentes : imagem corporal e relações sociais - Dias, Juliana Rocha Adelino (2013)
Adolescence is a period marked with numerous physical and social transformations. It is a stage of transition and preparation for entry into adulthood, during which the young student confronts new problems and is required new forms of social adjustment. Therefore, social relations, at this time of life, have attracted the attention of educators and researchers. This study aims to identify the social representations of adolescent students about adolescence, about the role of the body in social relations in the school and reflect on how these representations affect the involvement of female students with other school cultures. This work finds its methodological referential in Social Representation Theory, devised by Serge Moscovici (1978). The work contains the analysis of notions about school culture, using authors as: Candau (2010, 2011), Carrano (2011), Pérez Gómez (2001), Julia (2001), Viñao Frago (1995, 1996, 1998), Forquin (1993) and Vincent, Lahire and Thin (2001). The study also presents notions woven from authors like Coslin (2009), Daolio (1995), Keleman (1993), Le Breton (2007), Novaes (2010), Pereira (2005), among others, about adolescence, body and social relations. This is a qualitative study that included the participation of 66 students, aged between 15 and 17 years, enrolled in high school at a public school located in the city of Santos / SP. The data collection instruments used were: a) a questionnaire that aimed to access the profile of respondents, b) a test of free association of words c) a test with questions metaphorical and d) one theatrical performance followed by a debate (performed with part of the group - 11 students). Responses were treated by content analysis proposed by Bardin (1977). Methodological tools were used throughout the research allowing some inferences. With respect to the representations of adolescents, the subjects indicated that it is constructed and influenced by a historical produced vision at this fase of life, which associates the teenager with impulsiveness, as also, understands adolescence as a fase of preparation to the beginning of adulthood. The representations of the body are based in the assumptions of beauty and femininity circulated by society and transmitted by the media. As for social networking in the school environment, it was found that the representations are influenced by the body and its physical appearance. It was noted the complete absence of references to the school and its activities on ways of interaction between students. The research points to the need to deepen knowledge about the sub-cultures within the scope of the larger school culture.